HIGHER INCLUSIVE EDUCATION FOR PERSONS WITH SPECIAL EDUCATIONAL NEEDS AS A SOCIO-PEDAGOGICAL PROBLEM - Gavhar Saparovna Abdullayeva (Journal Park Publishing, 2022)
Higher education is one of the most effective ways of organizing life. It gives freedom of life choice, spiritual and material independence, forms a worldview and life goals, develops a person's ability to adapt to a changing social situation, gives life resilience and harmonizes existence, which is especially important for young people with disabilities.
Keywords: higher education, inclusive education, accessible information environment, psychological and pedagogical support, professional competence, adaptation of the higher education system.